Presence of Meaning in Life in Older Men and Women: The Role of Dimensions of Frailty and Social Support - Golovchanova, Nadezhda; Owiredua, Christiana; Boersma, Katja; Andershed, Henrik; Hellfeldt, Karin (Frontiers in Psychology, 2021)
Presence of meaning in life is an important component of eudemonic well-being while aging. While subjective health and interpersonal relationships are among important sources of meaning for older adults, less research has explored gender differences in the potential contribution of these sources to the presence of meaning in late life. The current study aims to examine the associations of frailty dimensions (daily activities, health problems, and psychosocial functioning) and social support with presence of meaning in late life, and whether these associations differ for older men and women. The study employs the data from the 65+ and Safe Study – a cross-sectional survey of residents of senior apartments. The data were collected in 2019 in a mid-sized Swedish municipality (N=618; age range from 64 to 106 years, 60.5% female). Results showed significant associations of health problems, psychosocial functioning, and social support with the presence of meaning in life. Further, results demonstrated no statistically significant gender differences in the associations between frailty dimensions, social support, and presence of meaning. However, since the interaction between health problems and gender approached statistical significance, this association was further explored indicating a more detrimental role of health problems in relation to presence of meaning in life among older men than among older women. Overall, the study highlights the importance of physical and psychosocial health and social support for presence of meaning in life among older adults and warrants further research on possible gender differences in the relation between health problems and meaning in late life.